PENGARUH KOMPOSISI MEDIA FERMENTASI (SARI UMBI TALAS : AIR) DAN INOKULUM STARTER TERHADAP MUTU PROBIOTIK - Marlina, Lusi; Mulyani, Nada Sri (UPPM Politeknik TEDC Bandung, 2025)
Taro (Colocasia esculenta) is a source of carbohydrates that is rich in nutrients, low in fat, low in calories, and gluten-free. Taro juice has the potential to be processed into functional beverages for the community. Increasing the functional value of the beverage can be done through fermentation with probiotic bacteria, resulting in a taro tuber juice probiotic beverage. Taro tubers provide nutrients that support the growth of lactic acid bacteria, such as Lactobacillus casei, which is commonly used in the production of probiotic drinks. This study aimed to evaluate the effect of fermentation media composition represented by the ratio of taro tuber juice and water, as well as the concentration of starter inoculum (Lactobacillus casei) on the quality of probiotic drinks produced. This study used a 2x4 factorial completely randomized design (CRD) method, with the first factor being the ratio of taro root juice and water (50:50 mL, 30:70 mL, 25:75 mL, 20:80 mL) and the second factor being the starter concentration (1%, 2%, 3%, 4%). Quality testing of the final product included pH analysis, total bacteria, total titratable acid, viscosity, and organoleptic evaluation (color, texture, aroma, and taste) based on SNI 7552-2009. The results showed that the best treatment in the production of taro root juice probiotic drink was obtained in the combination of taro root juice and water ratio of 30:70 mL with 4% starter concentration. This condition produced a product with a pH value of 5, total acid of 0.29%, viscosity of 12.83 cp, and organoleptic scores for color, texture, aroma, and taste of 2.8, 2.5, 2.9, and 2.5, respectively.